A Methods engineering study on Medz Shoes - Castillo, Corallie; Rodriguez, Cherrylene S.; Santos, Josephine C. (Diliman, Quezon City College of Engineering, 1999)
A study was done on the methods and systems and procedures of MEDZ Shoes Corporation, located at #3 Dragon St., Midtown Subdivision, San Roque, Marikina City. MEDZ Shoes is a sole-proprietorship owned by Mr. Francisco "Kiko" Medina. It manufactures shoes of good quality, comfortable to wear, and of affordable prices. It is currently a supplier of a large shoe company, JANEO and JANILYN's Shoes. A documentation of the present system, methods and processes were done through the use of different charting tools such as flow process charts, diagrams, two handed process charts, Ishikawa Diagram, and Streamline Analysis. A Time Study was also conducted using the company's present production process, and time standards for major operations were established. Findings and analysis shows that the company has many delays in its production. Problems addressed in the study were ineffective layout, unorganized storage of materials, and lack of systems forms. Alternative actions were generated and evaluated to come up with feasible solutions. The study persons recommended changes in the facility layout wherein transports were eliminated and minimized. The group recommended also a conveyor type of production for the Lasting Section to minimize the crisscrossing of paths on the shop floor. A centralized storage area was designed and racks appropriate for the materials are laid out. Regarding the problem on systems forms, a designed purchase order form and a logbook for inventory control is recommended. Unaddressed accountable causes of delays were stated for further study.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis